Development of auditory scene analysis: a mini-review - Calcus, Axelle (Frontiers in Human Neuroscience, 2024)
Most auditory environments contain multiple sound waves that are mixed before reaching the ears.In such situations, listeners must disentangle individual sounds from the mixture, performing the auditory scene analysis. Analysing complex auditory scenes relies on listeners ability to segregate acoustic events into different streams, and to selectively attend to the stream of interest. Both segregation and selective attention are known to be challenging for adults with normal hearing, and seem to be even more difficult for children. Here, we review the recent literature on the development of auditory scene analysis, presenting behavioural and neurophysiological results. In short, cognitive and neural mechanisms supporting stream segregation are functional from birth but keep developing until adolescence. Similarly, from 6 months of age, infants can orient their attention towards a target in the presence of distractors. However, selective auditory attention in the presence of interfering streams only reaches maturity in late childhood at the earliest.Methodological limitations are discussed, and a new paradigm is proposed to clarify the relationship between auditory scene analysis and speech perception in noise throughout development.